영어성경학습 교재 개발 및 적용: 예비 기독영어교사의 전공봉사학습 사례연구 - 최윤희; 이성희; Choe, Yoonhee; Lee, Sung-Hee (한국콘텐츠학회 논문지, 14(4), 2014)
This paper summarizes findings from investigations into the development and application of English bible study materials for middle school students in two local churches in Seoul, Korea. Six pre-service Christian English teachers have participated in the development of the materials. After the application of the new materials, the pre-service teachers' and bible study teachers' perception of the new materials have been investigated. To analyze the data, the pre-service teachers and bible study teachers were interviewed. The interview data was recorded, transcribed and analyzed based on content analysis method. The findings indicated that the pre-service teachers' church service learning gave them a sense of satisfaction and it also helped them develop professionalism in teacher education. To both the pre-service teachers and bible study teachers, keeping balance between bible teaching and English teaching was found to be a difficult task. The fact that the themes in the new materials are closely related to the lives of the students has been positively evaluated by the bible study teachers. 본 연구에서는 예비 기독영어교사들이 전공봉사학습의 일환으로 서울 소재 두 교회의 주일학교 중학생들을 대상으로 개발한 영어성경학습 교재를 실제 교육상황에 적용해 본 후, 예비 영어교사들의 교재개발 과정에 대한 인식과 주일학교 교사들의 교재에 대한 인식이 어떠한지를 살펴보고자 하였다. 본 연구에는 영어성경학습 교재 개발 과정이 단계별로 기술되어 있다. 본 연구의 자료 분석을 위해 예비 영어교사들과 주일학교 교사들과의 심층 인터뷰를 실시하였다. 인터뷰 내용은 녹음하여 전사하였고 내용분석 방법을 통해 분석하였다. 연구 결과, 예비 영어교사들의 영어성경학습 교재 개발 경험을 통한 전공봉사학습이 전공 전문성 향상은 물론 교회를 돕는 보람과 만족감을 갖게 한 것으로 나타났다. 성경학습 교재 내에서 성경교육과 영어교육 목표 사이의 균형을 이루는 것은 예비 영어교사들과 교재를 사용해 본 주일학교 교사들 모두에게 어려운 점으로 드러났다. 마지막으로, 주일학교 교사들은 교재 내의 학습활동들의 연계가 자연스럽지 못한 점을 한계로 인식하였으나, 교재의 소재가 학생들의 실생활과 밀접하게 연관되어 있는 점은 긍정적으로 인식하고 있었다.